Against violence : guidelines for counselling services and the police on dealing with violence in lesbian partnerships - Ohms, Constance (Frankfurt am Main : Lesbian Information and Counselling Service, 2002)
Fonds Suzan Daniel (FSD)
Engels
Monografie